Multisite Evaluation of Shock Incarceration: (Florida, Georgia, Illinois, Louisiana, Oklahoma, South Carolina, and Texas), 1987-1992 - MacKenzie, Doris Layton ([Verlag nicht ermittelbar], 1998)
This study analyzes shock incarceration (boot camp) programs in Florida, Georgia, Illinois, Louisiana, Oklahoma, South Carolina, and Texas. In each state, offenders who participated in boot camps were compared with demographically similar offenders who were sentenced to prison, probation, or parole. The impact of shock incarceration on offenders was assessed in two major areas: (1) changes in offenders' attitudes, expectations, and outlook during incarceration (self-report/attitude data), and (2) performance during and adjustment to community supervision after incarceration (community supervision data). The self-report/attitude data include variables measuring criminal history, drinking and drug abuse, and attitudes toward the shock incarceration program, as well as demographic variables, such as age, race, employment, income, education, and military experience. The community supervision data contain information on offenders' behaviors during community supervision, such as arrests, absconding incidents, jail time, drug use, education and employment experiences, financial and residential stability, and contacts with community supervision officers, along with demographic variables, such as age and race. In addition to these key areas, more detailed data were collected in Louisiana, including a psychological assessment, a risk and needs assessment, and a community supervision follow-up at two different time periods (Parts 11-18). For most states, the subjects sampled in the self-report/attitude survey were different from those who were surveyed in the community supervision phase of data collection. Data collection practices and sample structures differed by state, and therefore the data files are organized to explore the impact of shock incarceration at the state level. For each state, the unit of analysis is the offender.